Penggunaan Media Gambar Kartun untuk Meningkatkan Keterampilan Berbicara di Sekolah Dasar - Masruriyah, Jois Syahadati; Ngatmini (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to improve speaking skills using crtoon image based learning media for first grade students at SDN Pagonan. The type of research conducted is classroom action research. The subject of this study were seven first grade students at SDN Pagonan. This research was conducted in two cycles, each consisting of two sessions. Data collection techniques included observation, while data analysis used quantitative descriptive methods. The results of this studyvindicate that students speaking skills improved through the use of cartoon image media. This was evident fro the increase in the average achievement, which rose from a pre-action level of 62.85% to 71% in the first cycle, and further increased to 77% in the second cycle.